FROM A BINARY-STATE SYSTEM TO A MULTI-STATE SYSTEM - Ohi, Fumio (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
In this paper we present a survey of recent results about multi-state systems having totally ordered state spaces. Reviewing the definitions of important concepts in the theory of binary-state systems, we present how these concepts are generalized to the multi-state case and show significant results as stochastic bounds by minimal and maximal state vectors, stochastic bounds via a modular decomposition, stochastically ageing properties of multi-state systems and so on. Finally some issues for further studies are discussed.